2021
DOI: 10.3390/nu13061991
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Food on Instagram Social Network: Vegan, Homemade and Clean Eating

Abstract: Social media platforms have become part of many people’s lives. Users are spending more and more time on these platforms, creating an active and passive digital footprint through their interaction. This footprint has high research potential in many research areas because understanding people’s communication on social media is essential in understanding their values, attitudes, experiences and behaviors. Researchers found that the use of social networking sites impacts adolescents’ eating behavior. If we define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 141 publications
(187 reference statements)
1
35
0
4
Order By: Relevance
“…A similar study found that the longer the duration of internet use among Egyptian children and adolescents during COVID−19, the more likely they were to reduce their intake of vegetables, fruits, or protein ( 82 ). The Instagram Social Network can influence adolescents' eating behaviors ( 83 ) and shape eating trends ( 84 ). The duration of Instagram is significantly associated with dietary behavior ( 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…A similar study found that the longer the duration of internet use among Egyptian children and adolescents during COVID−19, the more likely they were to reduce their intake of vegetables, fruits, or protein ( 82 ). The Instagram Social Network can influence adolescents' eating behaviors ( 83 ) and shape eating trends ( 84 ). The duration of Instagram is significantly associated with dietary behavior ( 85 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the most researched categories are represented by “Diet” and “Cuisine”. A recent study by Pilar and colleagues [ 40 ] examined the diet topic on Instagram. The authors analyzed 2,045,653 messages created by 427,936 individual users, showing that users mostly associate healthy food with healthy lifestyle, diet, weight loss, and fitness.…”
Section: Discussionmentioning
confidence: 99%
“…These tests were conducted with the objective of measuring the state of individuals' mental health and suicide risk [21]. Additionally, more recent efforts have suggested the analysis of images from social media due to increased usage and influenceability of younger generations to these data types [106], [143], [144], as well as increased modern availability of computing power. Finally, research efforts such as the Durkenheim Project have implemented these analyses for assessing predictive suicide risk in individuals [19].…”
Section: Data Sourcementioning
confidence: 99%